Psychological and sociodemographic factors associated with hypoactive sexual desire in Ecuadorian women - Pérez-Vega, Doris; Subía-Arellano, Andrés; Buele, Jorge (Frontiers in Sociology, 2024)
IntroductionHuman sexuality is a multifaceted process, and sexual desire plays a central role in the triphasic model of the sexual response cycle, as proposed by Helen Singer Kaplan.MethodsIn this cross-sectional correlational study, we examined the relationship between various sociodemographic factors, such as age and motherhood, and sexual variables, including erotophobia, erotophilia, homophobia, and unconventional sex, with hypoactive sexual desire in women from Quito, Ecuador. The study sample comprised 421 women between the ages of 18 and 50, who were administered the Revised Sexual Opinion Survey and the Inhibited Sexual Desire Scale to assess their sexual attitudes and levels of desire.ResultsThe findings revealed that age (F = 7.13, p < 0.001) and motherhood (F = 13.72, p < 0.001) had a significant impact on inhibited sexual desire. Furthermore, significant correlations were observed between inhibited sexual desire and age (r = 0.16, p < 0.001), motherhood (r = 0.18, p < 0.001), erotophobia (r = 0.19, p < 0.001), erotophilia (r = −0.21, p < 0.001), and homophobia (r = −0.18, p < 0.001).DiscussionThese results suggest that women who are older, mothers, or have higher levels of erotophobia are more likely to experience hypoactive sexual desire. In contrast, higher levels of erotophilia and homophobia were inversely related to hypoactive sexual desire. This contributes to a deeper understanding of how different personal and sexual attitudes influence sexual desire in Ecuadorian women.